Mysidacea (crustacea) da comissão norte / nordeste I - Silva, Vera Maria Abud Pacífico da (1977)
Presents the sistematic and zoogeographical studies of eleven species of mysids, found in the samples collected by the "Almirante Saldanha" Oceanographic Ship in the North/Northeastern I Expedition during the period from 14/9 to 16/12, 1967. First we presented the material and methods used inboard and at tho Plankton Laboratory of the Zoology Department - UFRJ Biology Institute; then we wrote an abstract of the historical of the order with the brazilian occurrences. Further we rediscribed the species, given their occurrences and known geographical distribution. Yet we presented a list of the actual situation of the order in Brazil and based upon the results we suggest more researching studies about the group.